Granulomatous rhinitis secondary to feline leishmaniosis: report of an unusual presentation and therapeutic complications - Rodolfo Oliveira Leal; Hugo Pereira; Clara Cartaxeiro; Esmeralda Delgado; Maria da Conceição Peleteiro; Isabel Pereira da Fonseca (Journal of Feline Medicine and Surgery Open Reports, 2018)
Case summary A 12-year-old male neutered domestic shorthair cat underwent rhinoscopy due to inspiratory dyspnoea and stertor. Rhinoscopy showed signs of chronic rhinitis and a multinodular nasopharyngeal mucosa. A marked infiltrate of macrophages that contained intracellular parasitic forms morphologically compatible with Leishmania amastigotes were observed on histopathological examination of nasal and nasopharyngeal biopsies. PCR from nasal tissue was positive for Leishmania infantum DNA, confirming the diagnosis of granulomatous rhinitis secondary to this parasite. Two eyelid nodules were identified 2 weeks later. Fine-needle aspiration revealed Leishmania amastigotes within macrophages and in the background. Allopurinol therapy was started, but 5 days later the cat developed dermatological signs compatible with a cutaneous adverse drug reaction. The drug was discontinued and meglumine antimoniate prescribed. Twenty-five days later, the cat presented with acute kidney injury and meglumine antimoniate was discontinued. Despite clinical improvement after fluid therapy, mild azotaemia persisted. The cat was subsequently treated with nucleotides and active hexose correlated compounds (N-AHCC). Four months later upper respiratory signs were exacerbated. A relapse of granulomatous rhinitis was suspected and miltefosine therapy started. Chronic kidney disease (CKD) worsened during miltefosine treatment, having improved under fluid therapy. Since then, the cat has been treated with N-AHCC and renal diet and at the time of writing shows stable CKD with no recurrence of respiratory signs. Relevance and novel information This case describes Leishmania infantum as a cause of granulomatous rhinitis in a cat without cutaneous lesions, reporting the alternative use of N-AHCC and miltefosine when allopurinol seemed to have induced a cutaneous rash and there was acute kidney injury (AKI) after meglumine antimoniate therapy.